Community perceptions of behaviour change communication interventions of the maternal neonatal and child health programme in rural Bangladesh: An exploratory study - Rahman, Atiya; Leppard, Margaret; Rashid, Sarawat; Jahan, Nauruj; Nasreen, Hashima E (BioMed Central, 2016)
Background: This qualitative study explored community perceptions of the components of the behaviour change communication (BCC) intervention of the BRAC Improving Maternal, Neonatal and Child Survival (IMNCS) programme in rural Bangladesh. Methods: Semi-structured interviews, key informant interviews, focus group discussions and informal group discussions were conducted to elicit community views on interpersonal communication (IPC), printed materials, entertainment education (EE) and mass media, specifically (a) acceptance of and challenges presented by different forms of media, (b) comprehensibility of terms; printed materials and entertainment education and (c) reported influence of BCC messages. Results: IMNCS BCC interventions are well accepted by the community people. IPC is considered an essential aspect of everyday life and community members appreciate personal interaction with the BRAC community health workers. Printed materials assisted in comprehension and memorization of messages particularly when explained by community health workers (CHW) during IPC. Enactment of maternal, neonatal and child health (MNCH) narratives and traditional musical performances in EE helped to give deep insight into life’s challenges and the decision making that is inherent in pregnancy, childbirth and childcare. EE also improved memorization of the messages. Some limitations were identified in design of illustrations which hampered message comprehension. Some respondents were unable to differentiate between pregnancy, delivery and postpartum danger signs. Furthermore some women were afraid to view the illustrations of danger signs as they believed seeing that might be associated with the development of these complications in their own lives. Despite these barriers, participants stated that the IMNCS BCC interventions had influenced them to take health promoting decisions and seek MNCH services. Conclusions: Community based maternal and newborn programmes should revise BCC interventions to strengthen IPC, using rigorously tested print materials as aids and stand-alone media. Messages about birth preparedness (especially savings), recognition of danger signs and immediate self-referral to biomedical health services should be carefully aligned and effectively delivered to women, men and older members of the community. Messaging should utilize gendered storyline and address the seasonal cycles of conception, birth, antenatal, post-natal care and childhood illnesses. Future research should identify how best to combine IPC, printed materials, traditional cultural forms, and incorporate use of social media and mass media in different field situations.